PERAN FACEBOOK SEBAGAI MEDIA KOMUNIKASI PADA ORGANISASI SISYA VEDA SASTRA - Putri Niluh Wiwik Eka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The presence of increasingly sophisticated social media also clarifies the mutual relationship between communication and culture. Social media is able to help people connect with the surrounding as well as the world. Like the communication between teachers, members and alumni SVETA through facebook. Although they are in a long distance, Facebook is able to strengthen communication between one with another. The purpose of this study is to determine the role of facebook as a medium of communication in the organization SVETA. Methods used include interview techniques, questionnaires and documentation. The result of this research SVETA Organization (Sisya Veda Sastra) utilizing social media especially facebook to communicate between alumni and member of SVETA. Given the facebook function that allows many people to communicate, it would not be surprised if the majority of users of young people. Similarly with teachers, students and alumni SVETA, they use facebook applications to discuss and provide information related to organizational activities such as praying, funds punia, gotong royong, tirta yatra and others. The SVETA group activity in social media facebook include upload photos, status updates, comments, and chats about SVETA activities like Tirta Yatra, Dana Punia, discussions, and status updates. The conclusion of this research is interpersonal communication and small group communication in facebook able to strengthen the sense of brotherhood among teachers, members and alumni SVETA. Keywords: Facebook, Communication Media, SVETA Organization